Kasumba Turate As a Raw Material For Functional Herbal Drink - Nurfaillah, Nurfaillah; Yanto, Subari; Fadilah, Ratnawaty (Agricultural Technology Education Study Program, 2024)
Kasumba turate is one of the functional herbal plants because it contains polyphenols and high antioxidant activity. Dried kasumba turate flowers from farmers have varying concentrations in each plastic packaging so that it can affect the content of the steeped kasumba turate. This study aims to determine the effect of differences in concentration of kasumba turate on the quality of functional herbal drinks. The type of research used was a completely randomized design with a quantitative method consisting of one factor, namely the concentration of dried kasumba turate flowers. This study consisted of 3 treatments and 1 as control with 3 repetitions, namely: control (0.2 g), treatment A (0.6 g), treatment B (0.8 g), and treatment C (1 g). Each treatment was analyzed for moisture content, ash content, antioxidant activity (IC50 ), polyphenol content, total plate number, and organoleptic tests related to color, aroma and taste. The results showed that different concentrations of kasumba turate had a significant effect on the quality of functional herbal drinks based on water content, ash content, IC50 , polyphenol content, and taste organoleptic tests. 50The best treatment in this study was treatment C with a concentration of 1 gram of kasumba turate because it had an IC of 102.73 ppm in the medium category.